Problem Based Learning (PBL): Concrete Steps to Improve Students' Communication Skills - Najwa Nurfajriah; Imam Tabroni; Nursyifa Faujiah; Ridha Nurjannah; Tiara Putri (International Journal of Integrative Sciences, 2022)
Improving the communication skills of class XII students at Madrasah Aliyah Al-Manar Purwakarta need to use learning methods which in the learning process can encourage students to actively communicate. One of the learning models which in its implementation process encourages students to actively communicate is the Problem Based Learning (PBL) method. This study uses a quantitative experimental research approach. With experimental design Pre-experimental design is a design that includes only one group or class that is given pre and post tests. This one group pretest and posttest design was carried out on one group without a control or comparison group. The student data obtained in this study was from a test in the form of a questionnaire given to class XII students at MA Al-Manar Purwakarta. It can be concluded that the Problem Based Learning (PBL) method is effective in improving the communication skills of class XII students at MA Al-Manar Purwakarta